2015
DOI: 10.1159/000437361
|View full text |Cite
|
Sign up to set email alerts
|

Does Full Wound Rupture following Median Pilonidal Closure Alter Long-Term Recurrence Rate?

Abstract: Objective: The purpose of this study was to examine the recurrence rate of wound rupture in primary pilonidal sinus disease (PSD) after median closure. Subjects and Methods: A total of 583 patients from the German military cohort were interviewed. We compared the choice of surgical therapy, wound dehiscence (if present) and long-term recurrence-free survival for patients with primary open treatment, marsupialization and primary median treatment (closed vs. secondary open, respectively). Actuarial recurrence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…These procedures, which use different types of anaesthesia [ 2 ], are associated with advantages as well as disadvantages and may be associated with other cultural or geographical factors [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ], [ 8 ], [ 9 ]. In any case, minimal intervention is recommended, as it is said to be associated with short theatre times, cost efficiency, and superior outcome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These procedures, which use different types of anaesthesia [ 2 ], are associated with advantages as well as disadvantages and may be associated with other cultural or geographical factors [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ], [ 8 ], [ 9 ]. In any case, minimal intervention is recommended, as it is said to be associated with short theatre times, cost efficiency, and superior outcome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of a large cohort of PSD patients in the 1930s, the prevalence of women affected with PSD was around 20% 3 . An increasing number of studies reported during World War II noted a high prevalence of PSD in young male soldiers 4,5 . The military reported a lion's share of the disease burden, 6–8 and as mechanised warfare was new, the disease was referred to as ‘Jeep disease’ 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The military reported a lion's share of the disease burden, 6–8 and as mechanised warfare was new, the disease was referred to as ‘Jeep disease’ 4 . During this time period, the number of women serving in the army was very limited 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Our study clearly demonstrates that relapse is more dependent on time than operative technique, which explains the variability in the relapse rates we can find in the literature, likely because it depends on the time elapsed from surgery in the study (3, 11). In a recent analysis on 583 young adults with a 20-year follow-up, Doll et al found a 44% relapse rate of primary midline closure (25). In addition, studies show that the great majority of relapses occurs within 5 years from surgery (3, 11), because of that we compared our MIT group with our benchmark represented by the EPC group with a median follow-up of 5 years.…”
Section: Discussionmentioning
confidence: 99%